The duality of sport social workers coaching critical positive youth development within competitive youth sport - Tarr, C.; Newman, T. J.; Santos, F.; Turgeon, S. (International Sport Coaching Journal, 2023)
To meet the diverse needs of youth athletes within contemporary society, the privilege and responsibility of youth sport coaching must be reimagined. Critical positive youth development (CPYD)—which is grounded in Freire`s critical consciousness—emphasizes the urgency to empower youth to promote social justice and increase their ability to contribute to societal change. Considering the scarcity of CPYD in coach education, sport social workers may offer unique educational experiences and critical learning opportunities that may help fulfill a CPYD mandate within the youth sport landscape. From a social constructivist perspective, the aim of the current study was to explore the duality of sport social workers coaching competitive youth sport. Findings from 10 sport social workers suggest that the values, knowledge, and skills of the social work profession—particularly sport social work—seem to offer a transferable skillset and lessons to be emulated by CPYD coach education. For instance, because of their unique education and training, social workers are taught to use a strengths-based approach, maintain a holistic perspective, and teach life skills that contribute to PYD. However, findings also emphasize the notion that education may not solve all challenges concerning the need to foster CPYD, as many other variables make up the sport system.